Radio, telewizja i Internet jako instrumenty prowadzenia dyplomacji Stanów Zjednoczonych Ameryki Północnej = Radio, television and the Internet as instruments of conducting public diplomacy by the States of America - Glinka, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The United States of America are involved in broadly-understood activities in particular regions of the world. One of such activities is public diplomacy. In this context, there are well-founded reasons for a synthetic presentation of the main media: radio stations, TV stations, websites that fulfill the tasks of American public diplomacy. Especially if you consider the fact that the significance of such media's influence grows, on the one hand, with the increase of US' engagement on the global arena and, on the other hand, with the defining of American foreign diplomacy's priorities.
Keywords: Stany Zjednoczone Ameryki Północnej; media; dyplomacja